Exogenous tryptophan application improves cadmium tolerance and inhibits cadmium upward transport in broccoli (Brassica oleracea var. italica) - Jiang, Jia; Wang, Ze; Kong, Xiangzhou; Chen, Yajun; Li, Jing (Frontiers in Plant Science, 2022)
Cadmium (Cd) pollution not only reduces crop yields, but also threatens human health and food safety. It is of great significance for agricultural production to improve plant Cd resistance and reduce Cd accumulation. In Arabidopsis, tryptophan (Trp) has been found to play a role in Cd resistance. However, studies on the role of exogenous Trp on Cd tolerance in crops are limited. Here we report that exogenous Trp application can effectively alleviate biomass gradation induced by Cd stress and inhibit Cd transport from roots to shoots in broccoli. Compared to Cd stress alone, the fresh weight of shoots and roots of broccoli seedlings treated with Cd and Trp increased by 25% and 120% respectively, and the Cd content in shoots decreased by 51.6%. In combination with physiological indices and transcriptome analysis, we preliminarily explored the mechanism of Trp alleviating Cd stress and affecting Cd transport. Trp inhibited Cd-induced indole-3-acetic acid (IAA) conjugation, thereby providing enough free IAA to sustain growth under Cd stress; Trp inhibited the indolic-glucosinolates (IGS) biosynthesis induced by Cd. Considering that the synthesis of IGS consumes glutathione (GSH) as a sulfur donor, the inhibition of Trp in IGS synthesis may be conducive to maintaining a high GSH content to be against Cd stress. Consistent with this, we found that GSH content under Cd stress with Trp application was higher than that of Cd alone. In addition to alleviating the damage caused by Cd, Trp can also inhibit the upward transport of Cd from roots to shoots, possibly by repressing the expression of HMA4, which encodes a transporter responsible the xylem loading and Cd upward transport.